An object-oriented approach for context-aware applications - Fortier, Andrés (^p Datos electrónicos (1 archivo : 1152 KB))
In this paper we present a novel, object-oriented approach for designing and building applications that provide context-aware services. Our approach emphasizes a clear separation of the relevant concerns in the application (base behavior, context-sensitive properties, services, sensing technologies, etc.) to improve modularity and thus simplify evolution. We first motivate the problem with a simple scenario of a virtual campus; we next present a new context model, which emphasizes on behavior instead of data. We next show the main components of our architecture and a simple approach to achieve a clear separation of concerns. We analyze the most important (sub) models in which we decompose a context-aware application and explain the use of dependency mechanisms to achieve loosely coupled relationships between objects. We also show how to take advantage of a reflective environment like Smalltalk to adapt the application’s behavior dynamically and to provide transparent object distribution. We finally compare our work with others and discuss some further work we are pursuing.